Screening Mutagenic Strains with High Triterpene Content from Sanghuangporus baumii and Studying Their Antioxidant Capacity - YaWei Li; WenQi Xiao; XinYu Tong; NanNan Geng; TingTing Sun; Li Zou (Mycobiology, 2025)
To breed high-yield triterpene strains of Sanghuangporus baumii, the strain collected from the Heilongjiang Liangshui National Nature Reserve (DL101) was used as the starting strain. Protoplasts were mutated using ultraviolet light to screen for fast-growing mutant strains. Antagonistic experiments were conducted to observe the interactions between the mutant strains and DL101 and determine the triterpenes’ yield. Genetic differences between the strains were analyzed through Inter-simple Sequence Repeat (ISSR) molecular markers, and the antioxidant capacity of total triterpene extracts from the mutant strains was assessed in vitro. Results indicated that 340 regenerated mutant strains were obtained, among which 9 mutant strains were identified through antagonistic experiments. The mutant strains U-208, U-157, and U-275 showed total triterpene contents increased by 29.3%, 5.2%, and 1.3%, respectively, compared to DL101. ISSR analysis revealed genetic differences between mutant strain U-208 and DL101. in vitro antioxidant experiments indicated that the mutant strain U-208 exhibited higher antioxidant activity, and that there was a certain correlation between antioxidant activity and total triterpene content. This study utilized protoplast UV mutagenesis technology to obtain high-yield triterpene strains of S. baumii, providing excellent strains for the development and application of triterpene-related products.